Clinical Efficacy of Cervical Core Strengthening Exercise in the Treatment of Cervicogenic Headache - PEI Qian; GUO Xianfeng; HUANG Qiang (康复学报)
ObjectiveTo explore the clinical efficacy of cervical core strengthening exercise in the treatment of cervicogenic headache.MethodsA total of 168 patients with cervicogenic headache who visited Rehabilitation Medicine Department of Beijing Jishuitan Hospital from January 2016 to December 2017 were randomly divided into control group and treatment group using a random number table sampling method, with 84 cases in each group. The patients in the control group were treated with conventional treatment, including taking rest, treating with therapeutic modalities, oral drugs. Therapeutic modalities included ultrashort wave, interferential current therapy, laser, magnetic therapy (15 minutes per time, once per day). On the other hand, drug therapy included nonsteroidal anti-inflammatory drugs, eperisone hydrochloride and gabapentin, etc. In addition of the conventional treatment, the treatment group also participated in strengthening exercise of anterior, posterior and lateral core muscles of cervical vertebra (each movement held for 10 seconds, 20 movements at a time, and 5 sets of exercise per day) for 4 weeks. Furthermore, it was changed to 2 sets of exercise per day for 12 months. In addition, visual analog scale (VAS) score, Hamilton's Depression Scale-17 (HAMD-17), Pittsburgh Sleep Quality Index (PSQI) and Patients' Global Impression of Change (PGIC) scale were evaluated before treatment and at 1 month, 3 months and 12 months of treatment.ResultsIn terms of the intragroup comparison, the VAS score in control group improved at 1 month of treatment compared with that before treatment (P<0.05). There were no significant changes in each index at each time point (P>0.05). By contrast, the VAS, HAMD-17, PSQI and PGIC scores in the treatment group improved at 1 month, 3 months and 12 months of treatment compared with those before treatment (P<0.05). The comparison between groups showed that no significant differences were found in VAS, HAMD-17, PSQI and PGIC scores between the two groups at 1 month of treatment (P>0.05). Apart from that, the VAS, HAMD-17, PSQI and PGIC scores in the treatment group improved more than those in the control group at 3 months and 12 months of treatment (P<0.05). Specifically, at 3 months of treatment, the scores of the treatment group were VAS (2.96±1.11), HAMD-17 (25.95±5.91), PSQI (4.55±0.81), and PGIC (4.87±1.47), while the scores of the control group were VAS (5.86±1.31), HAMD-17 (36.97±7.62), PSQI (6.97±1.21), and PGIC (2.36±0.74), and the difference was statistically significant respectively (P<0.05). Last, at 12 months of treatment, the treatment group's VAS (1.92±0.91), HAMD-17 (21.94±7.52), PSQI (2.32±0.61), and PGIC (5.50±1.41) were better than the control group's VAS (6.97±1.01), HAMD-17 (41.38±9.02), PSQI (5.15±1.11), and PGIC (2.50±0.91), and the difference was statistically significant respectively (P<0.05).ConclusionThe cervical core strengthening exercise will relieve pain, improve scores of mood and sleep in patients with cervicogenic headache.